Informal commercial transactions: zone 8, “Bahía” zone, Colon and Pichincha streets. - Mayón, Starlyn (Revista Universidad de Guayaquil, 2015)
The research showed rates of informal trade in Guayaquil, “Bahía” zone, Colón and Pichincha streets, Zone 8, from the subject of Scientific & Business Research Methodology, Faculty of Administrative Sciences of the University of Guayaquil. Additionally to the research the team trained and managed the registration of informal-volunteers traders to Ecuadorian Simplified Tax System (ESTS). Informality in economic-commercial activities is a complex problem of great magnitude causing financial-monetary losses for the country, because one of the requirements to work in the informal sector is the smuggling of goods-inventory to be sold at low prices to consumers leading to tax evasion and unfair competition.A sample of 150 traders in the sector was chosen from a universe of 245, who helped us voluntarily for the success of this project; the Statistical Package for the Social Sciences was used to process the information. The student team required information from the Advising department from the Internal rental services, about the updating of government information, the same that was transferred to the informal traders. The legitimacy of informal traders guarantees job security, increased household incomes, deductible expenses grants. From there on they are considered reliable traders in tax affairs. All this is managed under the actions of the design-implementation of an action plan for the regulation and control of informal trading, contributing to the local economy and verifying that the information provided is accurate
Keywords: Informality; job security; tax; plan of action